Efektivitas Patroli Polisi Lalulintas Dalam Penanganan Kasus Kecelakaan Lalulintas di Kota Baubau (Studi pada Kantor Satuan Lalulintas Polres Baubau) - M Faris R; Mashendra; Hasiruddin H (DE FACTO : Journal Of International Multidisciplinary Science, 2026)
The objectives of this study are, first, to examine the effectiveness of traffic police patrols in handling traffic accident cases in Baubau City. Second, the study aims to identify the factors influencing the effectiveness of traffic police patrols in handling traffic accident cases in Baubau City. The research employs a normative legal research method, which focuses on the analysis of written legal norms, legal principles, and relevant court decisions. The findings indicate that traffic police patrols in Baubau City have been conducted regularly and are relatively effective in preventing and handling traffic accidents. However, their effectiveness still needs to be improved through the addition of personnel, the provision of adequate facilities and infrastructure, and increased public awareness. Furthermore, the effectiveness of traffic police patrols is influenced by the limited number of personnel and operational vehicles, low public awareness of traffic regulations, and inadequate road infrastructure. Therefore, strengthening human resources, providing adequate facilities and infrastructure, enhancing public education, and improving road infrastructure are necessary to optimize traffic patrol operations and reduce the incidence of traffic accidents.